Global Mass Spectrometric Analysis Reveals Chemical Diversity of Secondary Metabolites and 44-Methylgambierone Production in Philippine Gambierdiscus Strains - Malto, Zabrina Bernice L.; Benico, Garry A.; Batucan, Jeremiah D.; Dela Cruz, James; Romero, Marc Lawrence J.; Azanza, Rhodora V.; Salvador-Reyes, Lilibeth A. (Frontiers in Marine Science, 2022)
Surveillance and characterization of emerging marine toxins and toxigenic dinoflagellates are warranted to evaluate their associated health risks. Here, we report the occurrence of the ciguatera poisoning-causative dinoflagellate Gambierdiscus balechii in the Philippines. Toxin production and chemical diversity of secondary metabolites in G. balechii GtoxSAM092414, G. balechii Gtox112513, and the recently reported Gambierdiscus carpenteri Gam1BOL080513 were assessed using targeted and untargeted UPLC-MS/MS analysis and radioligand receptor-binding assay (RBA). 44-methylgambierone was produced by all three strains, albeit with different levels based on RBA and UPLC-HRMS/MS analysis. The fatty acid composition was similar in all strains, while subtle differences in monosaccharide content were observed, related to the collection site rather than the species. Molecular networking using the GNPS database identified 45 clusters belonging to at least ten compound classes, with terpene glycosides, carbohydrate conjugates, polyketides, and macrolides as major convergence points. Species-specific peptides and polyhydroxylated compounds were identified in G. balechii GtoxSAM092414 and G. carpenteri Gam1BOL080513, respectively. These provide a glimpse of the uncharacterized biosynthetic potential of benthic dinoflagellates and highlight the intricate and prolific machinery for secondary metabolites production in these organisms.